The Effect of Explicit Instruction of Meta Cognitive Learning Strategies on Promoting Iranian Intermediate Language Learners' Writing Skill - Ahmadi, Keramat; Ketabi, Saeed; Rabiee, Mitra (Theory and practice in language studies, 2012)
The present study was an attempted to investigate the effect of explicit instruction of meta-cognitive learning strategies on promoting intermediate language learners' writing skill. To achieve this purpose, an Oxford Placement test (Allen, 2004) was administered to language learners in English language institution and ultimately 24 intermediate language learners were selected and randomly assigned to an experimental group and a control group. Both groups worked on the same writing tasks and activities. The subjects in the experimental group were also instructed in the use of meta-cognitive language learning strategies following O'Malley (1985) while the subjects in the control group received some placebo treatment for a whole term. The results of the posttest showed that explicit instruction of meta-cognitive learning strategies for intermediate language learners proved effective. One reason may be that language learners at the intermediate level draw on these strategies in a conscious fashion and they need to develop a conscious awareness of the meta-cognitive learning strategies. [PUBLICATION ABSTRACT]